Dichotomous Keys Based on Cytogenetic Data for Triatomines Reported in Brazilian Regions with Outbreaks of Orally Transmitted Chagas Disease (Pernambuco and Rio Grande Do Norte) - de Mello, Denis Vinícius [UNESP]; Nhapulo, Emercio Felisberto; Cesaretto, Laura Poloto [UNESP]; Alevi, Julia Junqueira [UNESP]; Cristal, Daniel Cesaretto [UNESP]; Montanari, Giulia [UNESP]; Galvão, Cleber; Alevi, Kaio Cesar Chaboli [UNESP] (MDPI, 2023)
Chagas disease (CD) affects about eight million people worldwide. Brazil has the highest number of estimated cases and the largest number of deaths due to CD. Considering the recent outbreaks of oral CD involving at least 27 cases of acute CD in Pernambuco (PE) as well as 18 cases and 2 deaths in the Rio Grande do Norte (RN), we developed dichotomous keys for the identification of triatomine species in these Brazilian states based on cytogenetic data. All triatomine species could be distinguished by cytogenetic characteristics, emphasizing the importance of the newly developed taxonomic keys for the correct identification of triatomes from PE and RN, particularly for species that exhibit morphological similarities, such as Triatoma brasilensis and T. petrocchiae (present in both states) and T. maculata and T. pseudomaculata (as T. pseudomaculata has been misidentified as T. maculata in PE and RN). These alternative keys are expected to provide a useful tool for the scientific community and, above all, health agents, aimed at preventing mistakes from occurring in the identification of the vectors present in PE and RN related to CD outbreaks caused by oral infection.
Keywords: cytokey; taxonomy; triatominae